Expected Survival Using Models of Life Table Compared with Survival of Gastrointestinal Tract Cancer Patients in North of Iran - M Sheikh Fathollahi; M Mahmoodi; K Mohammad; H Zeraati (Tehran University of Medical Sciences, 2011)
Background: Northern regions of Iran have been encountered to dominate malignancies of gastrointestinal (GI) tract. We came to examine the total excess mortality due to the GI cancer in Mazandaran province. Methods: Socio-demographic and clinical data of 484 patients with GI cancer collected during the years 1990-1991were available from Babol Cancer Registry. Patients were followed up for 15 years by the year 2006. Using the West Coale-Demeny life table model, a number of five life tables for men and four for women, corresponding to each birth cohort, were constructed. Observed survival was obtained using the Kaplan-Meier method and compared with the Expected survival calculated using the direct adjusted method represented by STEIN et al. Results: The sample of subjects encompassed 66.3% men and 33.7% women with mean age 58.26 ± 10.90, and endoscopy was the general method for cancer detection. Esophagus accounted for 74.2%, and stomach and colorectal accounted for 22.7% and 3.1% of GI cancers, respectively. Survival rate in 15 years following diagnosis was nearly 6%. Comparing patient and expected survival curves showed a significantly reduced survival for patients of each GI cancer over the whole period and especially during the first two years after diagnosis. Conclusion: Patients experienced reduced survival associated with the development of GI cancers. Considering individuals in a population come from different cohorts, adjustment by constructing distinct life tables for different birth cohorts is recommended. The West model is recommended as a first choice to represent mortality in countries whose registration systems are exposed to various errors.